Characterisation of anticytoplasmic antibodies and their clinical associations. Issue 4 (April 1995) - Koh, W H; Dunphy, J; Whyte, J; Dixey, J; McHugh, N J
Abstract : OBJECTIVES–To characterise the cytoplasmic staining patterns identified by indirect immunofluorescence (IF) of human epithelial (HEp-2) cells and the antigens recognised using additional serological techniques. To define the disease associations of anticytoplasmic antibodies. METHODS–Sera from 1173 patients were screened for cytoplasmic IF staining on HEp-2 cells and the patterns characterised. The presence of antimitochondrial antibodies (AMA) was evaluated by a sensitive anti-pyruvate dehydrogenase complex enzyme linked immunosorbent assay (ELISA) (IgG) and by immunoblotting. Detection of antibodies to extractable nuclear antigens (ENA) was performed by double immunodiffusion and the presence of anti-ribosomal P antibodies was determined by immunoblotting. RESULTS–Cytoplasmic IF staining was demonstrated in 75 sera (6.4%). Six different patterns were recognised: coarse granular filamentous speckles (AMA, n = 9); condensed large speckles (anti-golgi apparatus antibodies, n = 3); cytoskeletal (n = 9); centriolar (n = 4); diffuse coarse speckles (n = 33); and fine speckles (n = 17). Of the nine sera with an AMA pattern, the presence of these antibodies was confirmed in seven by the ELISA (n = 6) and on immunoblotting (n = 7). One of the seven patients had primary biliary cirrhosis, and two had scleroderma. Two patients with anti-golgi antibodies had rheumatoid arthritis and two with anticentriolar antibodies had scleroderma. Of 33 sera that had cytoplasmic staining and were ANA negative, three were positive for anti-Ro and two were positive for anti-Jo-1 antibodies. CONCLUSIONS–In general, defined cytoplasmic IF patterns have no specific disease associations. However, the finding of cytoplasmic fluorescence should not be ignored, as it may indicate the presence of antibodies to ENA in the absence of nuclear staining.